Albanian Elements in the Slavic speech of Golo Bordo Bilinguals: Code-Mixing or Borrowing? - Morozova, Maria S. (Slověne, 2020)
The article considers contact-related phenomena found in the Slavic speech of bilinguals in the multiethnic region of Golo Bordo, Northeastern Albania. Most inhabitants of the Slavic part of the region master the local Western Macedonian dialect and the literary Albanian language. The material for the study includes dialect texts previously published in [Steinke, Ylli 2008; Соболев et al. 2013], examples from [Asenova 2016] and field materials collected by the author. Particular attention is paid to the insertion of Albanian nouns and verbs in the Macedonian speech of bilinguals. The article analyzes the ways to integrate the Albanian nouns, the examples of non-integrated verb insertions, and the models of adaptation of verbs. An attempt is made to provide a theoretical understanding of the described phenomena as either borrowing or code-mixing. The notion of “congruent lexicalization” [Muysken 2000] is used for the interpretation of phenomena such as the insertion of morphologically integrated Albanian nouns and non-integrated verbs used in their Albanian grammatical forms.